Re-Using Historical Aerial Imagery for Obtaining 3D Data of Beach-Dune Systems: A Novel Refinement Method for Producing Precise and Comparable DSMs - Jaime Almonacid-Caballer; Carlos Cabezas-Rabadán; Denys Gorkovchuk; Jesús Palomar-Vázquez; Josep E. Pardo-Pascual (Remote Sensing)
This study explores the potential of repurposing historical aerial photographs to produce high-accuracy digital surface models (DSMs) at regional scales. A novel methodology is introduced, incorporating road points for quality control and refinement to enhance the precision and comparability of multitemporal DSMs. The method consists of two phases. The first is the photogrammetric phase, where DSMs are generated using photogrammetric and structure from motion (SfM) techniques. The second is the refinement phase, which uses a large number (millions) of points extracted from road centrelines to evaluate altimetric residuals—defined as the differences between photogrammetric DSMs and a reference DSM. These points are filtered to ensure that they represent stable positions. The analysis shows that the initial residuals exhibit geographical trends, rather than random behaviour, that are removed after the refinement. An application example covering the whole coast of the Valencian region (Eastern Spain, 518 km of coastline) shows the obtention of a series composed of six DSMs. The method achieves levels of accuracy (0.15–0.20 m) comparable to modern LiDAR techniques, offering a cost-effective alternative for three-dimensional characterisation. The application to the foredune and coastal environment demonstrated the method’s effectiveness in quantifying sand volumetric changes through comparison with a reference DSM. The achieved accuracy is crucial for establishing precise sedimentary balances, essential for coastal management. At the same time, this method shows significant potential for its application in other dynamic landscapes, as well as urban or agricultural monitoring.